2019
DOI: 10.3389/fonc.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Postoperative Radiotherapy on Atypical Meningioma Patients: A Population-Based Study

Abstract: Purpose: It is controversial whether atypical meningioma patients undergoing gross-total resection (GTR) can benefit from postoperative radiotherapy (PORT). This study aimed to investigate the effectiveness of PORT on atypical meningioma patients.Methods: Patients diagnosed with atypical meningioma from 2008 to 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. The Kaplan–Meier survival curves were generated, and the log-rank test was used to compare the differences among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…It was showed that patients without PORT after STR had worse PFS ( 16 ). Recently, Chenyang Wang et al ( 30 ) found that PORT could significantly improve OS in AM patients who underwent STR ( 30 ), which was consistent with our previous finding ( 27 ). Currently, PORT has been routinely recommended for AM patients who underwent STR ( 6 , 31 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was showed that patients without PORT after STR had worse PFS ( 16 ). Recently, Chenyang Wang et al ( 30 ) found that PORT could significantly improve OS in AM patients who underwent STR ( 30 ), which was consistent with our previous finding ( 27 ). Currently, PORT has been routinely recommended for AM patients who underwent STR ( 6 , 31 ).…”
Section: Discussionsupporting
confidence: 87%
“…A recent study based on the National Cancer Database found that PORT and GTR were both associated with improved survival for AM patients ( 26 ). Whereas our recent study based on the Surveillance, Epidemiology, and End Results database found that PORT might not prolong the overall survival (OS) in AM patients undergoing GTR ( 27 ).…”
Section: Introductionmentioning
confidence: 93%
“…In the current meta-analysis, there was no statistical difference in pooled OS for any period between adjuvant RT and observation cohorts, in line with results of included individual studies [ 39 , 40 ]. Zeng et al have reported that the OS of AM patients who undergo GTR only is similar to that of patients who receive adjuvant RT after GTR or STR regardless of the extent of resection [ 40 ]. The extent of resection for AM can be an overwhelmingly significant factor to improve the OS, enough to conceal the effect of adjuvant RT.…”
Section: Discussionsupporting
confidence: 85%
“…The attrition bias was high in 11 studies with missing data because of restriction in follow-up duration or loss to follow-up for analyzing the outcome [ 3 , 10 , 30 , 35 , 36 , 39 – 43 , 45 ]. The risk of reporting bias was high in five studies that did not report the recurrence number or the percentage of each cohort [ 26 , 34 , 37 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…RT was significantly associated with shorter recurrencefree survival time (P<0.0001) but without impact on OS (P=0.88) (24). In previous study with a large sample size, adjuvant radiotherapy was not a prognostic factor for survival in the overall population (P=0.187), but for patients with subtotal resection, adjuvant radiotherapy significantly improved OS (P=0.026) (25). Wang et al showed a lower recurrence rate for patients treated with subtotal resection followed by adjuvant radiotherapy (P=0.023) (26).…”
Section: Adjuvant Radiotherapymentioning
confidence: 89%